Análise do retorno das ações ordinárias de empresas do setor energético nacional com participação do Governo no capital social - Damke, Berenice Righi (2017)
This study searches for internal and external factors that influence common stocks in the Brazilian energetic sector, in terms of excess return above the local risk free interest rate (CDI) and BM&FBovespa Stock Exchange Index (Ibovespa). It focus on understanding the Government influence when it is the main shareholder. The energetic sector was target on this study due to its high relevance for the economic growth. In Brazil, it is highly regulated and there is important participation of the local Government in the energetic sector’s companies. It is main shareholder in 35.5% of 45 companies of this sample. Where it was included 34 companies of energy generation and distribution and 11 companies of oil and gas (including Petrobras, which is a Brazilian icon), listed at BM&FBovespa, with liquid common stock between 2010 and 2016. It was analyzed the Government participation as the majority shareholder, as a proxy of low Corporate Governance, confirming this hypothesis. It was also shown that a increase in leverage, in terms of endebtness in its capital structure, brings negative impact in the stock excess returns. It was included several variables related to financial and accounting of the energetic sector companies, in addition to variables relative to the Brazilian economy. Many of them showed a low explicative power. However, GDP, foreign exchange rate BRL/USD, interest rates and inflation was proven to be significant, in line with prior studies about what influences common stock excess of return, in different sectors and countries, besides Brazil